Top-performing girls are more impactful peer role models than boys, teachers say - Sofoklis Goulas; Rigissa Megalokonomou; Panagiotis Sotirakopoulos (Proceedings of the National Academy of Sciences, 2025)
We examine teachers’ perceptions toward top-performing students and their role model influence on others in an online survey-based experiment. We randomly expose teachers to profiles of top-performing students and inquire whether they consider the profiled top performers to be influential role models. These profiles varied by gender and field of study (STEM or Non-STEM). Our findings show that teachers perceive top-performing girls as more influential peer role models compared to top-performing boys ( β ̂ = 0.289 ; P < 0.001 ). We also investigate the qualities teachers perceive top performers who are successful role models to have. We show that teachers associate a greater sense of learning autonomy and sense of being an example with top-performing girls compared to top-performing boys. Estimated effects are more pronounced among teachers with children and teachers in urban areas. Administrative data from a representative sample show limited observed differences between top-performing boys’ and girls’ educational outcomes that could justify the differences in teachers’ gender perceptions. These findings carry significant implications for education, as teachers play a crucial role in the cultivation of positive externalities between students.